Transnational Islam in Interwar Europe - Nordbruch, Götz. author. aut Link
VII, 250 p.
Keywords: The book examines Muslim-European interactions in the interwar period and provides original insights into the emergence of geopolitical and intellectual East–West networks that transcended national, cultural, and linguistic borders.